Linguistic Perspectives on the Construction of Meaning and Knowledge - Nolan, Brian; Diedrichsen, Elke (Cambridge Scholars Publisher, 2019)
This book is an exploration of the dimensions of meaning in language from several important perspectives that are of major interest to scholars today, bringing together studies from the realms of linguistic pragmatics, semantics, ontological knowledge engineering, and computational linguistics. Situated within modern functional-cognitive constructional-ontological and computational paradigms, the analyses here are supported by authentic language data, including corpus data, from a rich set of languages. Context and situation play an important but complex role in meaning elaboration.